Pressurised disc refining of wheat straw as a pre-treatment approach for agricultural residues: A preliminary assessment of energy consumption and fibre composition. (May 2020) - Skinner, Campbell; Baker, Paul; Tomkinson, Jeremy; Richards, David; Charlton, Adam
Highlights: Pressure refining wheat straw potential good route to accessing fermentable sugars. Scalable pre-treatment technology for agri-residues. Electricity demand around 160 kWh per tonne refined fibre DM at commercial-scale. Heat requirement 980–1900 MJ per tonne refined fibre DM. Non-fibre content of refined straw increased with increasing refiner pressure. Abstract: This preliminary study assesses a potential pre-treatment approach for agricultural residues, in order to improve enzyme access and cellulose digestibility that increased with increasing refining pressure. Wheat straw, an important European agri-residue, was chopped then refined at pilot-scale under different pressures (4–10 bar) and two refiner plate configurations. The most energy efficient runs used 0.94–0.96 kWh electricity; 8.9–11.0 MJ heat per kg dry matter fibre. A scaling factor specific to the machinery used in the trial suggested that wheat straw could be refined using approximately 160 kWh electricity and 980–1900 MJ heat per tonne DM yield at commercial-scale. Hemicellulose content in wheat straw at 31.8% decreased to the lowest level of 14.6% after refining at 10 bar. Pressurised disc refining did not appear to produce significant quantities of acetic acid, a key fermentation inhibitor, that could limit microbial fermentation.